Surgical treatment of primary and recurrent pterygium - I. A. Filatova; J. P. Kondratyeva; Yu. I. Borodin (Российский офтальмологический журнал)
Purpose: to study the results of surgical treatment and the course of healing of primary and recurrent pterygium.Material and methods. 97 patients (117 eyes) with varying degrees of pterygium, of which 58 were men and 39 women, were clinically observed for 1 to 3 years. The patients, aged 51.5 ± 4.2 on average, were divided into 3 groups depending on the degree of pterygium, the frequency of relapses and the type of surgical treatment.Results. It was shown that primary pterygium of the I degree should best be operated according to McReynolds method, pterygium of the II degree or higher should optimally be removed with conjunctival plastics by a free flap grafting, while for recurrent pterygium of the III degree or higher, combined treatment is recommended: removal of the pterygium using brachytherapy.Conclusion. For an adequate functional result of surgery, an individual approach is required for each case depending on pterygium proliferation stage.